2017
DOI: 10.1108/jaoc-03-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Management control systems

Abstract: Purpose This paper aims to examine the association between the interactive and diagnostic approaches to using controls and Miller and Friesen’s (1984) organizational life cycle (OLC) stages (birth, growth, maturity, revival). Design/methodology/approach Data were collected from a random sample of 343 general managers in Australian manufacturing organizations. Findings The results indicate that both approaches are used to a greater extent in the growth and revival stages than the birth and maturity stages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
10
0
2
Order By: Relevance
“…The interactive approach encourages the communication and can facilitate organizational learning and innovation. It can help the management to focus on critical performance variables which are linked to the implementation of organizational strategies (Dodge et al, 2017;Su et al, 2017).…”
Section: Management Control System and Family Firm's Innovation Perfomentioning
confidence: 99%
“…The interactive approach encourages the communication and can facilitate organizational learning and innovation. It can help the management to focus on critical performance variables which are linked to the implementation of organizational strategies (Dodge et al, 2017;Su et al, 2017).…”
Section: Management Control System and Family Firm's Innovation Perfomentioning
confidence: 99%
“…Furthermore, they argued that there were significant differences between small accounting practices and specifically how they addressed their contextual uncertainties. Su et al (2017) surveyed 343 general managers of Australian manufacturing organisations. They (2017) tried to explore relationships of Simon's (1995) integrative and diagnostic management control systems on organisational life cycle.…”
Section: Studies and Articlesmentioning
confidence: 99%
“…Their study revealed that social controls could improve procedural, distributive and interactional fairness. Su et al (2017) Relationships of Simon's (1995) integrative and diagnostic management control systems on organisational life cycle.…”
Section: Studies and Articlesmentioning
confidence: 99%
“…A solid PMS for diagnostic and interactive uses is required for an effective strategy execution (Arjaliès and Mundy, 2013; Su et al , 2017). PMS must be designed according to strategy to improve performance, (Vieira et al , 2016), because PMS aligns organizational activities with its strategy (Tucker and Parker, 2015) and communicates strategy to organizational members so that organizational goals can be better understood (Arjaliès and Mundy, 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%